Sponsees matter! How collective responsibility judgments of sport sponsors affect sponsee equity. Issue 5 (19th October 2020) - Dickenson, Peter; Souchon, Anne L.
ABSTRACT: Research question : Previous research has focused on sport sponsors, with little known on how sponsorship affects sponsee equity (e.g. audiences' behaviors towards sponsees). Further, sponsorship research typically ignores concurrent sponsors, which are naturally perceived in terms of perceived 'groupness' (entitativity). In turn, entitativity will affect people's judgments of the collective responsibility (CR) sponsors have towards the properties they are associated with. To compound the issue, sponsees' dependence on sponsors typically affords the latter authority that can also affect the CR people perceive sponsors have. We therefore examine how people's concurrent sponsors' entitativity and perceived authority influence sponsee equity through CR. Research methods : Data were collected from 255 (Study one) and 233 (Study two) consumers in a European country. Data collection consisted of scenario-based surveys. Responses were analyzed via structural equation modeling using Lisrel. Results and findings : We find that entitativity and perceived authority are related to people's inferences of omission, which consistently drives collective responsibility. However, the effect of inferences of commission on collective responsibility may be affected by the (non)official status of the sponsors. Meanwhile, entitativity and authority are also found to be linked to collective responsibility, which is itself related to sponsee equity. Implications : Theoretically, we advance knowledge of sponsee equity drivers by applying knowledge/theories from social psychology. Managerially, the findings suggest opportunities should be created for sponsors to be entitative and sponsors have an authority over the sponsee.